Islam in Post-communist Eastern Europe : Between Churchification and Securitization - Račius, Egdūnas, (Muslim Minorities ;, 2020)
In Islam in Post-communist Eastern Europe: Between Churchification and Securitization Egdūnas Račius reveals how not only the governance of religions but also practical politics in post-communist Eastern Europe are permeated by the strategies of churchification and securitization of Islam. Though most Muslims and the majority of researchers of Islam hold to the view that there may not be church in Islam, material evidence suggests that the representative Muslim religious organizations in many Eastern European countries have been effectively turned into ecclesiastical-bureaucratic institutions akin to nothing less than 'national Muslim Churches'. As such, these 'national Muslim Churches' themselves take an active part in securitization, advanced by both non-Muslim political and social actors, of certain forms of Islamic religiosity.